Pendidikan Karakter Berbasis Al-Quran - Dewi Purnamasari (Islamic Counseling : Jurnal Bimbingan dan Konseling Islam, 2017)
This article discusses the problem of character education. Character education into the spotlight of attention lately because of the decline, which resulted in the decline of morals. In the Qur'an, the characters use the term "akhlaq" who interpreted the will of the conditioned. Will and habit give rise to power. In the habit of producing a good deed is called akhlakul karimah. Character education is a deliberate effort to help character development with optimal. Character education can't just transfer knowledge or train a certain skill. Character education need to process, examples of exemplary, and conditioning or pembudayaan in the environment of the learners in the school environment, family, or community environment. Character education in the Qur'an need to pay attention to the importance of the cultivation of the moral dimensions of commendable (akhlakul karimah).